What’s the Missing Link? - Reviewing Climate Change Polices in Context of Indian Agricultural Sector - Mittal, Surabhi; Ray, Srabashi (Canadian Center of Science and Education, 2015)
Government of India has recently announced for special funds like National adaptation fund to handle market risks arising due to climatic variability. The operational protocol of this fund and other forthcoming initiatives have yet to be expanded, but through this paper we like to draw attention to some of the policies and programmes that the Governments of India have already initiated and that directly or indirectly link to managing the risks and challenges faced with climate change in context of agriculture sector. These policies have their own merits and demerits, but it is the need of the hour to draw synergies between the existing polices and new proposed actions to draw on the strengths of the ongoing programs and build up on that. This paper is also relevant in the context of UN Climate summit 2014 held on 23rd September and Food and Agriculture Organisation (FAO) aim at a global alliance for climate smart agriculture along with India’s prime ministers speech on 15th august, 2015 and the budget speech emphasising on threat that agriculture is facing because of climate change and government willingness to give emphasis on this agenda in context of agricultural sector. With the critical analysis, we also want to highlight the richness in the policy framework of several policies which are interlinked with each other, but due to lack of coordination they implementation might not be very appropriate.